Innovations in ventilative cooling - Chiesa, Giacomo; Kolokotroni, Maria; Heiselberg, Per (PoliTO Springer Series, 2021)
This book includes the most recent outcomes from research and professional practice in the ventilative cooling field, gathered by the selected panel of authors. It provides essential contents to face and reduce the rise of space cooling and ventilation energy uses in buildings by alternative ventilation and cooling solutions. The book is organised into three parts which include a detailed description of ventilative cooling boundaries and implications (working principles, KPIs, standards, comfort models, control techniques) and of principal techniques (night ventilation, controlled natural ventilation, hybrid solutions, PCM and mass activation, evaporative cooling, earth-to-air heat exchangers) along with an updated analysis of the background to the topic. Furthermore, the last part of the book defines a unique practical and theoretical framework to include ventilative cooling solutions in different building typologies along with their principal implications.